1983
DOI: 10.1007/bf01914088
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on the conformation of dibenzotropone adsorbed on montmorillonites

Abstract: The nature of the adsorption complex formed between dibenzotropone (OBT) and montmorillonite at elevated temperatures is strongly dependent on the interlayer cations. This was shown by electronic and IR spectra, by X-ray diffraction, and by study of the effects of gradual heating of the samples on these analyses. All samples exhibited significant red shifts of the electronic spectra of DBT into the visible range. These red shifts are attributed to two factors, both contributing to the enhancement of the tropyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…c-Met inhibitors are a class of small molecules that mediate the activation of several signaling pathways implicated in aggressive cancer phenotypes. The Katz group reported that certain 5H-benzo [4,5]cyclohepta[1,2-b]pyridin-5ones possess potent c-Met tyrosine kinase inhibitors both in vitro and in vivo. 278 MK-2461 (529) was the most potent compound and was efficacious in mouse tumor xenograft experiments.…”
Section: Review Syn Thesismentioning
confidence: 99%
See 1 more Smart Citation
“…c-Met inhibitors are a class of small molecules that mediate the activation of several signaling pathways implicated in aggressive cancer phenotypes. The Katz group reported that certain 5H-benzo [4,5]cyclohepta[1,2-b]pyridin-5ones possess potent c-Met tyrosine kinase inhibitors both in vitro and in vivo. 278 MK-2461 (529) was the most potent compound and was efficacious in mouse tumor xenograft experiments.…”
Section: Review Syn Thesismentioning
confidence: 99%
“…The Grauer group evaluated the effect of temperature on the conformation of 1 adsorbed on montmorillonites. 5 The IR spectra of complexes show that two factors contributed to the enhancement of the tropylium planar character of 5-dibenzosuberenone (1): hydrogen-bonding of acidic interlayer water to the carbonyl group, imparting positive charge to the tropone ring, and π interactions between the aromatic moiety and the oxygen planes. They also reported that 5-dibenzosuberenone (1) absorbed on dry silica gel exhibits a very large red shift in its electronic spectrum due to the formation of the planar aromatic tropylium cation 5 ( Figure 2).…”
Section: Introductionmentioning
confidence: 99%